Relasi Media-Negara-Masyarakat dan Pasar dalam Era Reformasi - Wahyuniï€ª, Hermin Indah (Jurnal Ilmu Sosial dan Ilmu Politik, 2000)
The withdrawal of state domination does not necessarily lead to the institutionalization of market. Freedom of information also requires a new kind of societal conduct. Indonesia currcntly faces tension in settling a triangular relationship between state, market and the society